2007
DOI: 10.1103/physrevd.76.056007
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion relations and subtractions in hard exclusive processes

Abstract: We study analytical properties of the hard exclusive processes amplitudes. We found that QCD factorization for deeply virtual Compton scattering and hard exclusive vector meson production results in the subtracted dispersion relation with the subtraction constant determined by the Polyakov-Weiss $D$-term. The relation of this constant to the fixed pole contribution found by Brodsky, Close and Gunion and defined by parton distributions is proved, while its manifestation is spoiled by the small $x$ divergence. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
106
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(110 citation statements)
references
References 28 publications
4
106
0
Order By: Relevance
“…(22) of Ref. [180]. Our formula (47), approximated to LO, expressed in momentum fraction space, and written down for CFF H, yields the aforementioned result and contains a prescription for treating the appearing divergencies.…”
Section: Note Addedmentioning
confidence: 99%
“…(22) of Ref. [180]. Our formula (47), approximated to LO, expressed in momentum fraction space, and written down for CFF H, yields the aforementioned result and contains a prescription for treating the appearing divergencies.…”
Section: Note Addedmentioning
confidence: 99%
“…Following Refs. [6,8], the subtraction function F q (0, t) can be related to the D-term form factor D q (t) [13] as follows…”
Section: Subtracted Dispersion Relations In the S-channelmentioning
confidence: 99%
“…In particular, DRs for Compton scattering processes, with both real and virtual photons, had wide applications for the prediction and extraction from experimental data of lowenergy properties of hadron systems [1][2][3][4][5]. More recently, the dispersion formalism has been extended to describe the virtual Compton scattering process in the deep inelastic region [6][7][8][9][10][11][12]. In particular, it was shown that the amplitudes for deeply virtual Compton scattering (DVCS) satisfy subtracted DRs at fixed t with the subtraction function defined by the D-term form factor [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By plugging the imaginary part of (8) into the subtracted DR (5) and equating it with the LO convolution formula (8) for the CFF, one can work out the GPD sum rule [13,14]:…”
Section: Fixed Pole Contribution In Gpd Frameworkmentioning
confidence: 99%